Monitoring temporal changes of the surface water area of the Burullus and Manzala lagoons using automatic techniques applied to a Landsat satellite data series of the Nile Delta coast - DEWIDAR, KH.M. (Mediterranean Marine Science, 2011)
This study introduces the automated shoreline techniques used to monitor the temporal change of surface water area of the Burullus and Manzala lagoons. In this study, a series of Landsat image data are acquired at intermittent intervals between 1972 and 2006 for the Burullus lagoon and between 1972 and 2007 for the Manzala lagoon. All Landsat images were radiometrically calibrated and converted to reflectance values. The reflectance values of each date were atmospherically corrected using the 6S model. The automated shoreline technique was checked against field observations by using GPS over the four seasons for each lagoon during reconnaissance for the shoreline boundary. The accuracy of the extracted shoreline boundary for each lagoon was validated by calculating the area of a big aquaculture farm in the study area from satellite imagery and the available topographic maps. The resulting accuracy of this technique used was approximately 97.5%. From the spatial temporal analysis of the satellite data, the results indicate that the rate change of aquatic surface area of the Manzala lagoon is –7.3 km2/yr and for the Burullus lagoon -2.7 km2/yr during the approximately 35 year period of study. The changes which were detected in this study indicate that the surface water area of Manzala lagoon and Burullus lagoon have decreased to 62.6% and 61.9 respectively of their original size during this time.